Using reflexive tools for coping and bringing closure in pediatric palliative care: A music therapist’s story of working with a terminally ill child. - Rigney, Maeve (Voices: A World Forum for Music Therapy, 2011)
This paper outlines the therapeutic journey of a newly qualified music therapist and a young girl with terminal cancer. As well as describing the clinical sessions with this young girl and her family, it includes personal reflections from the journal of the therapist, used as a method of self-review and clarification of thoughts and feelings following each session. The aim of this paper is to narrate the music therapy journey with Tina * from the music therapist's perspective, and to share my thoughts and feelings on coping while working with terminally ill children. In addition to outlining the significance of using reflexive tools for this type of work as a way to improve coping skills and to work more effectively when the future with your client is uncertain, I hope to encourage further others to share their work in pediatric palliative care.